(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article present the research outcomes of «Hanhyap» chicken species. The Biochemical indicators of chicken serum have been fixed and their adaptation was rated.